THE EVALUATION OF ECONOMIC EFFICIENCY OF PRODUCING AND SELLING SUNFLOWER SEEDS AT AGRICULTURAL ENTERPRISES OF UKRAINE - Перетятько, І. В. (Scientific Progress & Innovations, 2013)
Increasing demand for oilseeds in the world agricultural markets and in the agricultural market of Ukraine has been observing in resent years. Especially popular are sunflower seeds and derived products. That situation came under heightened scrutiny. This research examines the economic efficiency of production and selling sunflower seeds at agricultural enterprises of Ukraine. It is based on the Ukrainian summary statistical reports (2006–2011) and analyzes the main economic indicators of sunflower seeds production. The factors influencing performance of the enterprises in this profile are defined; the dynamics of sunflower seeds processing volume in Ukraine has been studied.